PENINGKATAN PRESTASI BELAJAR BAHASA INDONESIA MELALUI PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE PADA SISWA KELAS II SDN 2 DASAN LEKONG KECAMATAN SUKAMULIA TAHUN PELAJARAN 2020/2021 - SITI FATIMAH (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2021)
This Classroom Action Research (CAR) was conducted with the aim of knowing the improvement of Indonesian language learning achievement in poetry material through the application of the picture and picture learning model to Class II students at SDN 2 Dasan Lekong for the 2020/2021 academic year. This Classroom Action Research (CAR) was carried out in stages 2 cycles, and from the results of the actions that have been carried out it is proven to be able to improve student learning outcomes/achievements both in terms of classical student learning completeness, namely in the first cycle of 65%, it can increase to 90% in the first cycle. cycle II as well as in terms of the average value of the evaluation results, namely in the first cycle of How much to How much in the second cycle, this means that there is an increase of 25%. From the results of this classroom action research, it also showed an increase in the level of student learning activity from 3.2 quite active categories in the first cycle to 4.1 active categories, meaning there was an increase. ABSTRAKPenelitian Tindakan Kelas (PTK) ini dilakukan dengan tujuan adalah untuk mengetahui peningkatan Prestasi belajar bahasa Indonesia materi puisi melalui penerapan model pembelajaran picture and picture pada siswa Kelas II di SDN 2 Dasan Lekong Tahun pelajaran 2020/2021. Penelitian Tindakan Kelas ( PTK ) ini dilakukan dalam tahapan 2 siklus, dan dari hasil tindakan yang sudah dilakukan terbukti dapat meningkatkan hasil/prestasi belajar siswa baik dari segi ketuntasan belajar siswa secara klasikal yaitu pada siklus I sebesar 65%, dapat meningkat menjadi 90 % pada siklus II maupun dari segi nilai rata-rata hasil evaluasi yakni pada siklus I sebesar Berapa menjadi Berapa pada siklus II, ini berarti ada peningkatan sebesar 25 %. Dari hasil penelitian tindakan kelas ini juga menunjukkan adanya peningkatan tingkat aktivitas belajar siswa dari 3,2 kategori Cukup Aktif pada siklus I menjadi 4,1 kategori Aktif, berarti ada peningkatan.